Coffee Tradition - Suheri, Suheri (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2025)
This research explores the evolution of the coffee-drinking tradition from a private familial practice to a global medium for cross-cultural communication and social facilitation. Positioned as a symbolic bridge for cultural diplomacy, coffee is analyzed not merely as a commodity but as an egalitarian instrument for conflict resolution and trust-building. Adopting a constructivist paradigm with a qualitative approach, the study utilizes participant observation, in-depth interviews with cultural practitioners, and the Miles and Huberman interactive model for data analysis. The findings reveal that coffee serves as a